direct test of the effects of changing atmospheric pressure on the mating behavior of Drosophila melanogaster - Austin, Christopher J; Guglielmo, Christopher G; Moehring, Amanda J (Evolutionary ecology, 2014)
Changes in weather can be catastrophic for small insects. As such, it would be highly adaptive for insects to be able to sense when a weather front is approaching and respond appropriately. While correlative and anecdotal evidence exists that flies behaviorally respond to changes in barometric pressure, which indicate variation in weather, a direct test has yet to be performed. Here, we subject multiple strains of Drosophila melanogaster to changes in barometric pressure within a hypobaric chamber and measure male courtship and female receptivity. Since this species has a long copulation duration, copulating when adverse weather is approaching could subject both males and females to potentially lethal conditions. As predicted, some flies reduced their mating activity when exposed to a change in pressure that indicated imminent adverse weather. Surprisingly, however, some flies instead increased their mating activity; the behavioral response depended upon the strain’s native population location and intra-population variation, demonstrating that there is genetic variation for the behavioral response. This indicates that flies are able to anticipate weather patterns and change their behavior depending on the barometric pressure they experience, but that the form of behavioral response varies both within and between populations.